Mapping Global Publication Trends Studies on Artificial Intelligence: A Systematic Literature Review - Ika Malikatun Nisa; Salahudin Salahudin (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study aims to map the development of research and scholarly publications on Artificial Intelligence (AI) Governance, with a particular focus on policy, ethics, and regulatory frameworks. The review seeks to identify major research trends, the evolution of key themes, and the interconnections among topics within the global AI governance literature. A Systematic Literature Review (SLR) approach was employed following the PRISMA protocol to select relevant articles from the Scopus database. A total of 2,815 articles were identified and analyzed using VOSviewer and CiteSpace to examine keyword relationships, publication trends, and thematic structures that illustrate the intellectual landscape of AI governance research during the period 2019–2025. The findings reveal five major thematic clusters in AI governance studies: AI policy and regulation, digital governance and public administration, algorithmic transparency and trust, AI adoption and industry transformation, and ethics and accountability. Among these, AI policy and regulation emerges as the most dominant theme, indicating that policy and regulatory issues remain central to global AI governance discourse. In addition, the relationships among clusters highlight strong linkages between ethics, public trust, and digital transformation in shaping responsible AI governance systems. This study contributes both conceptually and methodologically to AI governance research by providing a comprehensive mapping of global scholarly trends and thematic structures. However, the study is limited by its reliance on a single database (Scopus). Future research is therefore encouraged to incorporate additional databases such as Web of Science and EBSCO to expand the scope of analysis.